Paraneoplastic Cerebellar Degeneration Associated with Breast Cancer: A Case Report and a Narrative Review - Rosario Luca Norrito; Maria Grazia Puleo; Chiara Pintus; Maria Grazia Basso; Giuliana Rizzo; Tiziana Di Chiara; Domenico Di Raimondo; Gaspare Parrinello; Antonino Tuttolomondo (Brain Sciences, 2024)
Paraneoplastic neurological syndromes (PNSs) are an uncommon complication of cancer, affecting nearby 1/10,000 subjects with a tumour. PNSs can involve all the central and peripheral nervous systems, the muscular system, and the neuromuscular junction, causing extremely variable symptomatology. The diagnosis of the paraneoplastic disease usually precedes the clinical manifestations of cancer, making an immediate recognition of the pathology crucial to obtain a better prognosis. PNSs are autoimmune diseases caused by the expression of common antigens by the tumour and the nervous system. Specific antibodies can help clinicians diagnose them, but unfortunately, they are not always detectable. Immunosuppressive therapy and the treatment of cancer are the cornerstones of therapy for PNSs. This paper reports a case of PNSs associated with breast tumours and focuses on the most common paraneoplastic neurological syndromes. We report a case of a young female with a clinical syndrome of the occurrence of rigidity in the right lower limb with postural instability with walking supported and diplopia, with a final diagnosis of paraneoplastic cerebellar degeneration and seronegative rigid human syndrome associated with infiltrating ductal carcinoma of the breast.